URGENSI INDEPENDENSI HAKIM PERSPEKTIF HUKUM ISLAM - Umam, Khoerul (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2024)
The judge is the enforcer of the law in deciding all matters faced by the state. The position of a judge isa very important position for any country to grow, if law enforcement by a judge can proceed in accordance with the law and render justice to the people then the state will receive its share. The judge in carrying out his position as law enforcement is not only fixed to legislation legislation by the government, but there is an obligation for the judge to look into the legal values of the living community so that the decisions that society will receive are in accord with a sense of justice. In view of the importance of the role of the judge as well as the great effect of the office of judge, a judge must keep his freedom of judgment in judgment, for when an intervening judge then affects the ruling he renders would in no way be proper and illegal so that the determined justice would never be realized. The standard of the urgency of an independent judge became important to formulate, one through islamic law